Remimazolam for preventing sevoflurane-induced emergence delirium after pediatric laparoscopic inguinal hernia repair: a placebo-controlled randomized clinical trial - Yiwen Lu; Guangbin Liang; Yan Lu; Jingjing Wang; Jianhang Mo; Zhiyuan Chen; Ruizhao Shao; Kui Hu; Ping Pang; Xiaoxia Gu (Jornal de Pediatria)
Objective: To investigate the effectiveness and safety of remimazolam in preventing the emergence of delirium in children undergoing pediatric laparoscopic inguinal hernia surgery under combined intravenous and inhalation anesthesia. Methods: A total of 184 pediatric patients aged 3–14 years who were undergoing laparoscopic inguinal hernia surgery were included. Patients were randomly assigned to receive either 0.1 mg/kg remimazolam (experimental group, n = 92) or 0.9 % normal saline (control group, n = 92) after the procedure. The primary outcome was the incidence of emergence delirium, which would manifest as a difference in the pediatric anesthesia emergence delirium (PAED) score between the two groups. The secondary outcomes included postoperative pain severity, duration of postanesthesia care unit (PACU) stay, sufentanil usage, parental satisfaction, mean arterial pressure (MAP), blood oxygen saturation (SpO₂), and heart rate (HR). Results: The experimental group showed significantly lower overall PAED scores (mean difference = −2.28, 95 % CI:2.73 to −1.82; Cohen's d = 1.12, p < 0.001) and emergence delirium incidence (7.61 % vs 41.30 %; risk difference = 33.69 %, 95 % CI 21.60 % to 45.10 %; relative risk = 0.18, 95 % CI 0.09–0.37; p < 0.001). They also showed better hemodynamic stability (lower MAP/HR, higher SpO₂), reduced pain, shorter PACU stay, less sufentanil use, and higher parental satisfaction (all p < 0.05). Conclusion: Administration of 0.1 mg/kg remimazolam after pediatric laparoscopic inguinal hernia surgery could contribute to preventing the development of emergence delirium by smoothing hemodynamic changes and alleviating postoperative pain.